دور أبعاد الذكاء التنظيمي في تطوير أداء شركات التأمين (دراسة ميدانية على شركات التأمين الخاصة في الساحل السوري( - قاسم, سامر; كنعان, علي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى دراسة مدى توافر أبعاد الذكاء التنظيمي في شركات التأمين الخاصة في الساحل السوري، ودراسة طبيعة وقوّة العلاقة التي تربط بين أبعاد الذكاء التنظيمي والأداء. ولتحقيق ذلك تمّ صياغة ثلاث فرضيّات، واستخدم الباحث أسلوب الاستبانة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample T. test، واختبار الارتباط الثّنائي Pearson Correlation، واختبار الانحدار البسيط. وقد توصل الباحث إلى عدّة نتائج أهمّها: يتوافر الذكاء التنظيمي في الشركات المدروسة بتقييم جيد، كما توجد علاقة طردية موجبة بين أبعاد الذكاء التنظيمي والأداء، ويوجد تأثير ذو دلالة احصائية للذكاء التنظيمي على الأداء في الشركات محل الدراسة. The study aims to study the availability of the dimensions of organizational intelligence in the private insurance companies in the Syrian coast, and study the nature and strength of the relationship between the dimensions of organizational intelligence and performance. To achieve this, three hypotheses were formulated. The researcher used the questionnaire technique to collect the data analyzed using statistical tests, the most important of which were: the one-sample T. test, the Pearson Correlation test, and the simple regression test. The researcher found several results, the most important of which is: Organizational intelligence in the studied companies is well evaluated, there is a positive relationship between the dimensions of organizational intelligence and performance, and there is a statistically significant effect of organizational intelligence on performance in the companies under study.